Analysis of Electric Field for HDPE-NR Biocomposite using Finite Element Method - Tong, Chung Yan; Mohd Jamail, Nor Akmal; Shee Kandar, Mohd Haris Asyraf; Othman, Nordiana Azlin; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2020)
In developing future electrical networks, it is crucial to develop new alternatives insulating materials which can improve the performance of the next generation high voltage cables. The high electric field reduces the resistance of solid insulation and causes partial discharge occurs through the impurities in a dielectric where this phenomenon causes ageing to the dielectric and ultimately leads to breakdown. Thus, this paper seeks to analyse the electric field intensity of High Density Polyethylene (HDPE) when added with 10%, 20% and 30% of different types of bio-filler such as coconut coir fibre, pineapple leaves fibre, and oil palm empty fruit bunch. This can be achieved by creating a two-dimensional (2D) axisymmetric electrostatic model by using the Finite Element Method Magnetics (FEMM) 4.2 software. The results showed that the inclusion of bio-filler in HDPE increased the maximum electric field intensity when compared with unfilled HDPE. The electric field intensity also varied with the different percentages loading of biocomposite and their permittivity. As a result, the maximum electric field intensity was much lower for HDPE added with a 10% loading of the oil palm empty fruit bunch. Hence, oil palm empty fruit bunch was the best composition as it tends to improve the dielectric properties since it has a lower electric field intensity at the top sphere electrode as compared to other compositions.